2022
DOI: 10.1002/jbm.a.37430
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cell seeding technique and cell density on BMP‐2 production in transduced human mesenchymal stem cells

Abstract: Small animal models have demonstrated the efficacy of ex vivo regional gene therapy using scaffolds loaded with BMP‐2‐expressing mesenchymal stem cells (MSCs). Prior to clinical translation, optimization of seeding techniques of the transduced cells will be important to minimize time and resource expenditure, while maximizing cell delivery and BMP‐2 production. No prior studies have investigated cell‐seeding techniques in the setting of transduced cells for gene therapy applications. Using BMP‐2‐expressing tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…Cell seeding on to osteoconductive scaffolds remains a critical step for any cell‐based therapy for bone healing with numerous factors contributing to optimal cell dispersion including cell number and seeding technique. Previously, our in vitro study demonstrated that transduced ASCs had improved seeding efficiency and homogeneity of cell distribution with lower density of cells, and that dynamic seeding with the orbital shaker technique had a higher BMP‐2 production per cell despite lower cell seeding efficiency 21 . We hypothesized that fewer cells loaded with the orbital shaker technique could have similar total BMP‐2 production and therefore fewer cells could be used to heal a segmental bone defect when subsequently adapting this model for use in patients.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Cell seeding on to osteoconductive scaffolds remains a critical step for any cell‐based therapy for bone healing with numerous factors contributing to optimal cell dispersion including cell number and seeding technique. Previously, our in vitro study demonstrated that transduced ASCs had improved seeding efficiency and homogeneity of cell distribution with lower density of cells, and that dynamic seeding with the orbital shaker technique had a higher BMP‐2 production per cell despite lower cell seeding efficiency 21 . We hypothesized that fewer cells loaded with the orbital shaker technique could have similar total BMP‐2 production and therefore fewer cells could be used to heal a segmental bone defect when subsequently adapting this model for use in patients.…”
Section: Discussionmentioning
confidence: 86%
“…Human adipose tissue was harvested from the fat pad of healthy patients undergoing total knee arthroplasty at our institution. The stromal vascular fraction (SVF) was obtained according to previously published protocols 21,22 . Briefly, the fat pad was extensively washed with Dulbecco's PBS (DPBS, Lonza, Basel, CH) to remove red blood cells and debris.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, seed cells are required to have the ideal ability to proliferate and secrete extracellular matrix (ECM). Seeding techniques such as static seeding, negative pressure seeding, centrifugal seeding, spinner flask, orbital shaker, and perfused bioreactor can be used to seed cells onto the scaffolds to promote articular cartilage regeneration [ 42 - 44 ] . The commonly used seed cells in cartilage tissue engineering and the effects of cell density in the scaffolds will be discussed below.…”
Section: Scaffold Componentsmentioning
confidence: 99%
“…Other studies focus on modifying the surface of the scaffolds, which can be done by chemical etching [515], plasma treatment [356], or immobilizing cell binding motifs such as the peptide sequence arginineglycine-aspartate [516]. More complex dynamic seeding methods such as negative pressure, orbital shaking or perfusion have also been described, but those are more relevant for constructs with remarkably inaccessible surfaces, such as constructs displaying intricate interconnected pores or the inside of tubular scaffolds [254,517]. Another way in which we could improve our approach would be by implementing a way to directly measure the contractile force of the cardiac minitissues, instead of having to rely on parameters extracted from video analysis.…”
Section: Increasing the Biological Representativity Of Cardiac Miniti...mentioning
confidence: 99%